A roadmap for the successful use of social media in electoral campaigns - Pratama, Awanda S. S.; Danan, Elloy Y. M. S.; Angeline, Grace; Abdillah, Irfan Z.; Prayoga, Jevin A.; Jabari, Nedal A. M. (Association for Scientific Computing Electrical and Engineering, 2021)
Over the last few years, social media has become important for many people and can affect many aspects of life. In terms of politics, social media can help candidates and political parties do their political campaign. The use of social media in politics and during political campaigns has become a vital part for every political party and candidate. This paper describes the current social media and its characteristics, how campaigns were conducted in the past and how modern campaign activities were conducted. Case studies from several countries regarding how political campaigns were carried out are also written in this paper. The authors explore the factors available in social media that can affect and change the political process and campaign. Strong and weak factors of using social media in electoral campaigns are also discussed in this paper. This paper further addresses the author's point of view about how candidates should use social media during elections.